Cervical artery dissection - วัชระศักดิ์ศิลป์ กนกวรรณ (Journal of Thai Stroke Society, 2019)
Cervical artery dissection is an important cause of stroke in young adults. CAD can occur related to trauma or spontaneously. CAD are more likely to occur in the extracranial part of vessel even it can occur in both extracranial and intracranial. The dissections are characterized by separation of the arterial wall between the layers of the intima and media by a haematoma, which may be secondary to an intimal tear or from rupture of the vasa vasorum. Cerebral ischemic is an important complication which result from thromboembolism or hypoperfusion of dissected vessels. Treatment options concern for the secondary prevention have been debated for years due to little randomized trial evidence. Most neurologists favor anticoagulants, but a minority prefer antiplatelets. New evidence of clinical went out but still need more question to resolve